Dispersion and re-agglomeration phenomena during melt mixing of polypropylene with multi-wall carbon nanotubes - Jamali, S. (2013)
The present work reports study of the dispersion and re-agglomeration of carbon nanotubes in a polymer melt using a prototype mixer that enables precise control over the processing parameters. Since dispersion of CNT in polymer matrices has been comprehensively studied in the literature, the focus here is to understand the spatial or temporal evolution of the process. Dispersion showed a far from gradual evolution and good correlation with the composite electrical resistivity. The effect of composite reprocessing on nanotube re-agglomeration and subsequent dispersion was also investigated. A large nanotube re-agglomeration was detected on composite re-melting, matching an increase in electrical resistivity. However, the efficiency of reprocessing in terms of rate and level of dispersion depends on the thermo-mechanical stresses created during the initial processing stage, as shown by data obtained for processing at two shear rates, and reprocessing performed at lower, identical and higher shear rates.